2019
DOI: 10.7717/peerj.7501
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of subsoil physicochemical and microbial properties by short-term fallow practices

Abstract: Fallow management can improve the soil nutrients in the topsoil and upper subsoil. However, little is known about the effects of short-term (one year) fallowing with different treatments, such as vegetation and fertilization, on subsoil (20–40 cm) properties. We conducted field trials to explore the changes in subsoil properties in response to such treatments in the Yellow River Delta region in China. Different vegetation and fertilization treatments were applied, and we measured the carbon and nitrogen conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
1
3
0
Order By: Relevance
“…Fertilization significantly improved the relative abundance of Lysobacter while decreasing the relative abundance of Gemmatirosa and Afipia (Figure 3b). Our observation on Lysobacter was similar to that of other studies on alkaline saline alluvial soil, acidic black soil, or alkaline loess soil [73][74][75]. This may be due to the fact that bacteria of the genus Lysobacter have a good ability to colonize the root periphery of crops [76,77].…”
Section: Phod-harboring Bacteriasupporting
confidence: 89%
“…Fertilization significantly improved the relative abundance of Lysobacter while decreasing the relative abundance of Gemmatirosa and Afipia (Figure 3b). Our observation on Lysobacter was similar to that of other studies on alkaline saline alluvial soil, acidic black soil, or alkaline loess soil [73][74][75]. This may be due to the fact that bacteria of the genus Lysobacter have a good ability to colonize the root periphery of crops [76,77].…”
Section: Phod-harboring Bacteriasupporting
confidence: 89%
“…It should be noted that native vegetation fallow with manure also increased microbial biomass N because plant diversity could promote nutrient-use efficiency [31]. In existing studies, this management method is also considered to be a relatively effective fallowing management method; however, considering its high cost, there may be some resistance in its actual implementation [13,25]. The analysis results of the different bacteria genera between the groups in the late fallow period showed that F-irrig, M-irrig, and M-ferti had the most obvious differences from the control group.…”
Section: Microbial Properties Changes Caused By Fallow Managementmentioning
confidence: 99%
“…Combined with the relationship between the bacterium and microbial nitrogen, it can be seen that the increase in microbial nitrogen can inhibit nitrogen consumption and promote the growth of surface vegetation [40,41]. The bacterium Steroidobacter is closely related to denitrification, and it is negatively correlated with the microbial biomass carbon content and the microbial biomass carbon-nitrogen ratio, indicating that the control group is more likely to cause the emergence of denitrification, and the microbial biomass carbon content is low [13,42].…”
Section: Microbial Properties Changes Caused By Fallow Managementmentioning
confidence: 99%
See 1 more Smart Citation